Pengaruh Bimbingan Guru Pendidkan Pancasila dan Kewarganegaraan Terhadap Penggunaan Media Sosial Pada Peserta Didik - Suherman, Ade; Dewi, Hilda Cahayati; Hermanto, Odang (CV. Kurnia Grup, 2024)
The use of social media can affect the characteristics of individuals, especially students who are still in the developmental stage. Therefore, guidance from PPKn teachers, as character education teachers, is needed to prevent the occurrence of deviant behavior due to unethical use of social media. This study aims to determine the extent of the influence of PPKn teachers' guidance on the ethical use of social media by students. The type of research used by the researcher is descriptive research using a quantitative approach. The population of this study is the tenth grade students of SMAN 8 Garut, with a sample of 60 tenth grade students obtained through simple random sampling techniques. a) The study found that PPKn teachers employed several methods to guide the use of social media, including teaching, reminding, discussing, and encouraging students to use social media properly. b) The obstacles faced include limited time, the content itself where students are unable to filter what is on social media, and the inability of PPKn teachers to monitor students constantly and independently. c) Efforts made include maximizing time in class, reminding, assigning tasks, interacting with students on social media, and providing direct examples. d) There is an influence of PPKn teachers' guidance on the ethical use of social media by students.